2018
DOI: 10.1016/j.envint.2018.09.052
|View full text |Cite
|
Sign up to set email alerts
|

Urinary trace metals individually and in mixtures in association with preterm birth

Abstract: One in ten infants born in the United States is born preterm, or prior to 37 weeks gestation. Exposure to elevated levels of metals, such as lead and arsenic, has been linked to higher risk of preterm birth (PTB), but consequences of lower levels of exposure and less studied metals are unclear. We examined the associations between 17 urinary trace metals individually and in mixtures in relation to PTB. The LIFECODES birth cohort enrolled pregnant women at <15 weeks gestation at Brigham and Women’s Hospital in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(36 citation statements)
references
References 55 publications
(67 reference statements)
1
35
0
Order By: Relevance
“…The limit of detection (LOD) and proportion of samples below the LOD for each exposure biomarker are included in Additional File 1 : Supplemental Table 1. For biomarker concentrations that were below the limit of detection, machine-read values were used in this analysis [ 44 ]. When reported values were less than zero or blank, the value was imputed as LOD/√2 [ 45 ].…”
Section: Methodsmentioning
confidence: 99%
“…The limit of detection (LOD) and proportion of samples below the LOD for each exposure biomarker are included in Additional File 1 : Supplemental Table 1. For biomarker concentrations that were below the limit of detection, machine-read values were used in this analysis [ 44 ]. When reported values were less than zero or blank, the value was imputed as LOD/√2 [ 45 ].…”
Section: Methodsmentioning
confidence: 99%
“…Two different mechanisms have been proposed to explain Cu-induced oxidative damage in the human body: (1) free Cu can catalyze the formation of hydroxyl radicals—powerful reactive oxygen species (ROS) that can damage cellular DNA, membranes and proteins [ 42 , 83 , 84 ]; and (2) increased levels of Cu may suppress the availability of glutathione, a highly abundant cellular antioxidant [ 85 ]. Cu was also associated with higher odds of preterm birth in the Puerto Rican population in our study [ 38 ] and in a pregnant women cohort in Boston [ 48 ], and it is possible that Cu impacted the early parturition through pathways including oxidative damage.…”
Section: Discussionmentioning
confidence: 77%
“…Analysis was performed at NSF International (Ann Arbor, MI, USA), where concentrations of 21 metals and metalloids were measured: Arsenic (As), barium (Ba), beryllium (Be), cadmium (Cd), cobalt (Co), chromium (Cr), cesium (Cs), copper (Cu), mercury (Hg), manganese (Mn), molybdenum (Mo), nickel (Ni), lead (Pb), platinum (Pt), Sb, tin (Sn), titanium (Ti), tungsten (W), uranium (U), vanadium (V), and zinc (Zn). Metal(loid) concentrations were measured using inductively-coupled plasma mass spectrometry (ICPMS) as described previously [ 48 ]. Considering that biological samples have high levels of carbon and chloride in the matrix, the laboratory selected the appropriate isotopes for the requested elements to best avoid interferences where possible.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pregnant women are in a critically important state for susceptibility to metal effects because of hemodynamics, hormone changes, and immature immune systems (7), and metals could further affect fetal growth after passing through the placental barrier (8). Studies have found that prenatal exposure to certain ranges of manganese (Mn) (9), copper (Cu) (10), lead (Pb) (11), zinc (Zn) (12), and magnesium (Mg) (13) is linked to adverse birth outcomes, including small-forgestational-age (SGA) births, low birth weight, and preterm delivery. Similarly, low-level prenatal Pb exposure, as well as elevated Mn and Zn levels, might increase the risk of preterm birth and SGA (14).…”
Section: Introductionmentioning
confidence: 99%